Job Interest and Work Readiness Among Islamic Vocational Students: Minat Pekerjaan dan Kesiapan Kerja di Kalangan Siswa Sekolah Kejuruan Islam - Ratnasari, Rigelita; Indriani, Ririn Dewanti Dian Samudra (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Youth unemployment remains a persistent challenge in Indonesia, particularly among vocational high school graduates. Specific background: Despite vocational schools being designed to prepare students for the labor market, many graduates still face difficulties due to low work readiness. Knowledge gap: Limited research has explored the psychological aspects, specifically the role of job interest, in shaping students’ readiness for employment within Islamic vocational contexts. Aims: This study investigates the relationship between job interest and work readiness among Class XII students at SMK Islam Roudlotus Saidiyyah Semarang. Results: Using a saturated sampling of 95 students and psychological measurement scales, the analysis with Pearson’s product moment correlation revealed a strong and significant relationship (rxy = 0.756, p < 0.05). Higher job interest was consistently associated with higher levels of work readiness. Novelty: This study highlights the substantial contribution of job interest (57.2%) to work readiness in Islamic vocational education, offering empirical evidence rarely addressed in similar contexts. Implications: Findings suggest that fostering job interest through curriculum design and career guidance could serve as a strategic approach to strengthen students’ readiness for the workforce. Highlight: Job interest strongly correlates with work readiness. Contributes 57.2% to student readiness. Provides insights for Islamic vocational education. Keywords: Job Interest, Work Readiness, Psychology, Islamic Vocational School, Students